Avaliação do desempenho de cadeias de produtivas da agricultura familiar – o caso do leite in natura em Quixadá/Ceará - Nunes, Rosângela Venâncio (2009)
The agricultural familiar production is presented as a very important segment inside of the which had national economy to its paper in the food production, generation of work, job and income and occupation of the land. However, this segment has characterized for an inadequate organization and management, compromising its competitiveness. In Ceará, the chain of the milk of familiar agriculturists is ones of most important as for the generation of work, job and income in the agricultural way. However, it presents low productivity of the raw material (milk in natura) necessary for the industrial transformation. Due to lack of resources and consistent strategies of market, the small milk producers of the Ceará are not organized enough in order to have the due access and good performance in the market. In this context, the performance analysis constitutes an analytical instrument of great utility, therefore it can supply given of great value the taking of decision, being of great importance under the prism of the agricultural management, in view of that it can more allow to the familiar agriculturist the adjusted use of the resources with that it operates. Resources that are scarces and limited. So it is necessary the application of techniques and methodologies to guarantee the good performance of the resources in order to reach optimum possible return for its investments. Of this form, the familiar agriculturist if does not have to come back only toward its experience, but to evaluate the performance of its production and to take measured corrective. In view of the displayed one, this research is presented whose main objective is on the basis of to evaluate the performance of the productive chain of milk in natura familiar agriculture in Quixadá/Ceará. In methodologics terms, the research is characterized as exploitative, applied, descriptive with boardings quantitative and qualitative, using itself of bibliographical techniques of research, documentary research and research-action. It developed itself from six main stages: (i) Definition of the Problem, Subject to inquire and Intents of the Research; (ii) Detailing of the Methodology of the Research To be applied (iii) Construction of the Theoretical References; (iv) Characterization of the Productive Chain of Milk in the Ceará and election of the Pointers to be Used in the Interviews (v) Accomplishment of the Study of Case with analysis of the Performance of the Chain through the Collected Pointers (vi) Elaboration of the Conclusions and Recommendations. One expects that this research serves as subsidy for other works in the area of evaluation of small agricultural enterprises, therefore the evaluation elements and considered improvement of performance in this research can be useful for assistance projects technique, agricultural extension, cooperatives, associations and agencies financiers, a time that considers a methodology of evaluation and improvement of performance, so contributing for organization of based systems of production in familiar agriculture.